Leaders assemble! : leadership in the MCU - Schmidt, Gordon B.; Islam, Sy (Exploring effective leadership practices through popular culture, 2022)
In this volume of Exploring Effective Leadership Practices through Popular Culture, Schmidt and Islam examine how you can learn about research and evidence-based leadership concepts through examples drawn from the popular MCU movies and related superhero films. Leaders Assemble! Leadership in the MCU includes sound research and evidence-based advice on how to improve as a leader on topics such as leadership development, conflict management, mentorship, sensemaking, shared leadership, servant leadership, authentic leadership, servant leadership, and selecting your team. Examples from your favorite MCU films make these concepts come alive so you can easily see how they can be used to improve your own leadership skills. Each chapter focuses on a core leadership concept and shows you how you can use it to be a successful leader, with MCU films and superheroes leading the way with relevant examples, before finally summarizing the main points you can use in your own leadership practice.